Indios, Moradores e Câmaras Municipais: Etnicidade e conflitos agrários no Rio de Janerio e no Espírito Santo (séculos XVIII e XIX) - Losada Moreira, Vânia Maria (2012)
This paper analyzes the processes of extinction of indigenous collective lands and villages in Rio de Janeiro and Espírito Santo, from mid-eighteenth century to the nineteenth century, giving emphasis on the role of IndigenousÆs policy aiming to delay the process. Based on the correspondence among authorities, laws, statistical reports, and petitions from the Indians themselves, we approach the agrarian conflicts among indigenous, non-Indian residents and municipal councils, focusing on the issue of controversies and discussions regarding ethnicity that played a central role in these disputes.